TINJAUAN KRITIS DISKURSUS PENERAPAN GREEN TAX DALAM PERSPEKTIF KHALIFATULLAH FIL ARDH - Annisa, Azizatun; Septyan, Krisno (Universitas Islam Negeri Imam Bonjol Padang, 2023)
This study aims to criticize the practice of green tax within the framework of human nature as a caliph on earth. This research used a humanist-theocentric approach that started from understanding human nature (fitrah) first. The results of this study showed that the application of green tax essentially deviated from the core objectives of green tax. Instead of improving the environment, it turns out that it is not purely for environmental improvement, but for the business environment. The application of green tax ultimately betrayed the noble purpose of human nature on its own earth. This paper hopefully will become an afterthought (muhasabah) and change the point of view that has dimensions of worship in green tax implementation so it is pure to protect the earth.